Interaction between pellet properties and blast furnace operation - Leimalm, Ulrika (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2010)
The raw material properties of iron-bearing material and coke have a significant impact on the blast furnace (BF) process. The raw materials are designed and chosen to achieve smooth BF operation but the operational parameters can be simultaneously modified to meet properties of selected raw materials. As the pre-set process conditions change, e. g. due to an increase in pulverized coal injection rate (PCR), the in-furnace conditions for iron oxide reduction change, burden distribution pattern has to be adapted and demands on raw material strength will be affected, etc. In order to maintain stable operation, but also to obtain low amounts of material losses through the off-gas, it is important to understand fines generation and behaviour in the blast furnace. The present investigation focuses on how the pellet properties during reduction can affect the BF process as well as how pre-set process conditions will influence pellet properties. The performed tests involve full-scale, pilot and laboratory investigations.Raw material sampling of, among other things, pellets was carried out during a period of fluctuations in the hot metal Si content at the SSAB BF No. 3 at Luleå. Although differences in pellet low-temperature reduction disintegration and the high-temperature breakdown were observed, the reduction behaviours during laboratory blast furnace simulation tests were almost identical. Differences in the hot metal Si content in a production blast furnace were difficult to correlate to raw material properties, since the process conditions were changed in order to control the heat level of the blast furnace. Tests in the LKAB Experimental Blast Furnace (EBF) were carried out under different pre-set process conditions. Injection of high-volatile (HV) coal resulted in a higher reduction potential in the ascending gas due to a higher H2 content and an increased shaft temperature compared to operation with low-volatile (LV) coal. A higher pellet reduction degree was attained in pellets sampled with the upper shaft ...